X-RAY FLUORESCENCE MEASUREMENT OF IRON ACCUMULATION IN SKIN AS A SURROGATE MARKER FOR IRON LEVELS IN CRITICAL ORGANS AND TOTAL BODY IRON BURDEN - Dao, Erica (My University, 2017)
This thesis investigates the use of x-ray fluorescence (XRF) measurements of skin iron concentration as a non-invasive surrogate marker for total body iron burden. Rats were overloaded with iron dextran via intraperitoneal injection to investigate trends in iron accumulation in skin and organs. The skin, heart, liver, and kidney of the animals were collected and the iron concentrations were measured using the Huber XRF system and the polarized energy dispersive x-ray fluorescence (PEDXRF) system. When measured in the Huber XRF system, a very strong quadratic correlation was found between skin iron concentration and liver iron concentration (R2=0.92). In the same system, skin iron concentration had a moderately strong linear correlation with heart and kidney iron concentration (R2=0.53 and R2=0.65, respectively). Measured in the PEDXRF system, heart and kidney iron concentrations were again linearly correlated with skin iron concentrations (R2=0.34 and R2=0.31, respectively). Liver iron concentration again showed a quadratic correlation with skin iron concentration (R2=0.64). Therefore, it was demonstrated that skin iron concentrations can act as a surrogate marker for organ iron concentrations in rats, especially for the liver. The feasibility of using an Olympus Innov-X Delta Professional Handheld XRF Analyzer, a commercial portable x-ray fluorescence (PXRF) device, as a tool for in vivo skin iron analysis was investigated. The same rat skin samples measured in the previous experiment were measured using the PXRF device and compared with the organ iron concentrations as measured using the Huber XRF system. The heart and kidney showed linear correlations with skin iron concentration (R2=0.45 and R2=0.36, respectively). The liver showed the strongest correlation with a moderately strong quadratic correlation with R2=0.74. It was determined that using Beam 3 in the Soil mode of this device resulted in equivalent and effective dose rates of 230±10mSv/min and 2.3±0.1mSv/min, respectively. Thus, the PXRF device has shown promise as a potential tool for measuring in vivo skin iron levels.
Keywords: x-ray, iron, x-ray fluorescence, skin, liver, thalassemia